Optical quantum electromagnetic binormal Heisenberg landau lifshitz electromotive microscale - Korpinar, Talat; Korpinar, Zeliha; Yeneroglu, Mustafa (Springer, 2024)
In this manuscript, we design quasi optical Landau Lifshitz electromotive quasi microscales according to quasi frame. Thus, we establish optical binormal electromagnetic Landau Lifshitz microscales by using magnetic optimistic density in quasi Heisenberg space. Also, we receive binormal quasi optical Landau Lifshitz optimistic density in quasi Heisenberg space. Finally, we investigate electromagnetic Landau Lifshitz electromotive quasi microscales by optical quasi electroosmotic potentials in Heisenberg space.
Keywords: Optical quasi frame; Optical Landau Lifshitz microscale; Landau Lifshitz model; Electromotive quasi microscale